THE NURSING HOME VISIT IN THE FAMILY HEALTH STRATEGY (FHS) IN VIEW OF ELDERLY AND FAMILIES (Fiep Bulletin - online, 2013)
This study aims at describing the home visit (HV) held by the FHS nurse in the perspective of elderly and relatives to identify the identified problems and interventions taken by the nurse in nursing home visit. It is a descriptive and exploratory study, which involved 76 elderly and relative residents in a given area from Unit for Family Health, the west district of Natal-RN city. We used a simple random sample of the type (10% of elderly), who answered the forms during the period from March to June 2006. Results show that 67.10% of the elderly are visited monthly by health professionals of FHS, most by community workers (97.37%) followed by doctors (36.84%) and nurses (17.10%). The home visit from the nurse in relation to other professionals is held to a lesser extent, and sometimes only when necessary and/or at the request of the family. According to elderly and relatives, the nursing interventions are made more on education: the guidelines regarding nutrition, hygiene care, and actions that improve the venous circulation, as well as on the practice of moderate exercises. Among the identified health problems, it is highlighted osteomuscular (27.5%) and Projeto de Assistência Interdisciplinar ao Idoso em Atenção Primária % Orientações sobre alimentação,e cuidados gerais de higiene-38,08% Orientações sobre posições e ações para facilitar a circulação corporal e exercícios (principalmente caminhadas)-15,48% Orientações sobre hipertensão e verificação de pressão arterial-22,62% Vacinação e procedimentos clínicos (curativos, sondas, retirada de pontos)-7,14% Orientações sobre como realizar os tratamentos terapêuticos e prescrevê-los segundo programas de saúde-7,14% Solicitação de exames e encaminhamentos- hypertension (21.3%). The results also show that despite the nurse showing a low indicator of HV, develops actions of prevention and health promotion and home visit is an important tool that helps in this process. It is believed that the reduced frequency of home visits conducted by the nurse is in line with other tasks that he/she performs or due to the limited number of professionals to meet an increasing demand for elderly by low complexity actions.
Keywords: home visit; elderly; nurse